MaternaI mortality in West Africa: from epidemiology to public health - (:unkn) unknown (My University, 2000)
Since the "Safe Motherhood Initiative" was launched in 1987, the epidemiology of maternal morbidity and mortality is better known. At this end of the XXtrh century, maternal mortality is at the same level in West Africa than it was in Europe in the XVIIIth century. Moreover, it does not seem to have decreasedsince two decades, even in major cities where are concentrated both the qualified personnel and the technical means. The study of maternal morbidity has revealed a high incidence of severe obstetrical morbidity, responsible for a high letality. Since, in cities, maternal health services are largely used by the pregnant women, this letality points to a poor quality of those services. We demonstrated a poorquality of the prenatal consultation (screening for risk factors and iron supplementation) but also a scientific error as to the potential role of prenatal care. Relationships between the midwives, many doctors and the pregnant women are bad : violence, disdain and lack of adequate care are common. lnaddition, few deliveries are effectively performed by midwives even in cities, where they are in sufficient numbers. Ethic is often poor. Although this situation is well known by govemments in West Africa, no organized action has been undertaken. This lack of political will or the incapacity to transform it into actions is analysed. Responsibility is 'shared by West African govemments and donor agencies. Based on this analysis, propositions are made to move towards a matemity at lesser risk.
Keywords: African Research